Germline HAVCR2 mutations altering TIM-3 characterize subcutaneous panniculitis-like T cell lymphomas with hemophagocytic lymphohistiocytic syndrome. (December 2018) - Gayden, Tenzin; Sepulveda, Fernando; Khuong-Quang, Dong-Anh; Pratt, Jonathan; Valera, Elvis; Garrigue, Alexandrine; Kelso, Susan; Sicheri, Frank; Mikael, Leonie; Hamel, Nancy; Bajic, Andrea; Dali, Rola; et al.
Abstract Subcutaneous panniculitis-like T cell lymphoma (SPTCL), a non-Hodgkin lymphoma, can be associated with hemophagocytic lymphohistiocytosis (HLH), a life-threatening immune activation that adversely affects survival1, 2 . T cell immunoglobulin mucin 3 (TIM-3) is a modulator of immune responses expressed on subgroups of T and innate immune cells. We identify in ~60% of SPTCL cases germline, loss-of-function, missense variants altering highly conserved residues of TIM-3, c.245A>G (p.Tyr82Cys) and c.291A>G (p.Ile97Met), each with specific geographic distribution. The variant encoding p.Tyr82Cys TIM-3 occurs on a potential founder chromosome in patients with East Asian and Polynesian ancestry, while p.Ile97Met TIM-3 occurs in patients with European ancestry. Both variants induce protein misfolding and abrogate TIM-3's plasma membrane expression, leading to persistent immune activation and increased production of inflammatory cytokines, including tumor necrosis factor-α and interleukin-1β, promoting HLH and SPTCL. Our findings highlight HLH–SPTCL as a new genetic entity and identify mutations causing TIM-3 alterations as a causative genetic defect in SPTCL. While HLH–SPTCL patients with mutant TIM-3 benefit from immunomodulation, therapeutic repression of the TIM-3 checkpoint may have adverse consequences. This study finds germline loss-of-function mutations inHAVCR2, which encodes the immune modulator TIM-3, in individuals with subcutaneous panniculitis-like T cell lymphomas and hemophagocytic lymphohistiocytosis, a life-threatening inflammatory condition.